Highly dense and textured superconducting (Bi, Pb)2Sr2Ca2Cu3O10+δ ceramic samples processed by spark-plasma texturing. Issue 11 (15th August 2016) - Pérez-Acosta, L.; Govea-Alcaide, E.; Noudem, J.G.; Machado, I.F.; Masunaga, S.H.; Jardim, R.F.
Abstract: Consolidated powders of the superconducting cuprate Bi1.65 Pb0.35 Sr2 Ca2 Cu3 O10+ δ (Bi-2223) by the spark-plasma texturing (SPT), spark-plasma sintering (SPS), and the traditional solid-state reaction method were investigated by several techniques and their features compared. The results show that SPT samples exhibit a higher degree of texture, as inferred by a Lotgering factor of ∼0.73 along the [00 l ] direction and a relative density of 96% of the theoretical value. From magnetic hysteresis loops M vs. H at 5 K, the intragranular critical current densities along two applied magnetic field orientations, J c 0 c and J c 0 ab, relative to the compacting pressure direction, were determined. The anisotropy factor, γ J = J c 0 ab / J c 0 c, yielded an estimate of ∼2 in the SPS sample and ∼19 for samples obtained via the SPT method. In the latter samples, J c 0 c at 5 K is close to 1.3×10 8  A/cm 2, a value higher than others found for the same compound. The temperature dependence of the electrical resistivity, ρ ( T ), analyzed within the framework of a current conduction model for granular superconductors, supports the higher degree of texture of SPT samples and indicates changes in the oxygen content when samples are subjected to a post-annealing heat treatment. All the results reveal the promising capabilities of the SPT method for improving volume density, texture, and grain boundary connectivity of superconducting Bi-2223 materials.